Smartphone Camera as a Marketing Icon: Roland Barthes' Analytical Approach to Advertising Strategies - putra, Yuda syah; Riana, Irpan (Jurnal Ilmiah Publipreneur, 2023)
ABSTRACT                                                      This article delves into the role of smartphone cameras as marketing icons through the analysis of Roland Barthes' perspective on advertising strategies. The primary focus is to explore how smartphone cameras serve not only as functional tools but also as cultural symbols influencing consumer perceptions. The main objective of this article is to elucidate the marketing strategies of smartphone cameras through Barthes' conceptual framework, identifying signs and symbols used in advertisements, and investigating their impact on modern consumer culture. The article also aims to provide in-depth insights into how positive and emotional images are crafted to reinforce the position of smartphone cameras as marketing icons. The research methodology employs Roland Barthes' analytical approach, particularly the concept of semiotics, to dissect the advertising structure of smartphone cameras. Case studies are used to provide concrete and comprehensive examples of how marketing strategies are implemented in smartphone camera advertisements. The analysis results indicate that smartphone cameras are not merely utilized as technological tools but are also constructed as symbols of status and self-expression. Advertising strategies successfully create myths surrounding smartphone cameras, influencing consumer perceptions and shaping a positive image deeply rooted in consumer culture. In conclusion, it can be inferred that smartphone camera marketing goes beyond technical features, leveraging symbolic concepts to create a deeper allure. This conclusion underscores the importance of understanding semiotic aspects in advertising to unearth broader implications related to consumer culture and the dynamics of marketing technological products.